A Deflection-Based Bridge Diagnosis Method. (28th July 2009) - Yang, Xiaofan; Zhang, Chunming; Chen, Weimin
Abstract : By exploiting the "correlation of deflections" phenomena, we propose a new bridge diagnosis method. First, we introduce the notion of deflection correlation (DC) graphs and propose a method for building a DC graph. Second, we present a new algorithm for locating the abnormal cliques. Finally, we demonstrate the potential utility of the new method by applying it to the simulated diagnosis of a real-life bridge.